From belief to knowledge : achieving and sustaining an adaptive culture in organizations - Douglas, Neil , 1962-; Wykowski, Terry S. (Taylor & Francis, 2011)
Offers organizational leadership with a way to bring about a culture conducive to the growth of knowledge - one that reflects an improved fit of culture to the existing environment. This book addresses the need for a deeper analysis of learning in organizations that goes beyond looking at knowledge as an asset